2016
DOI: 10.4269/ajtmh.15-0420
|View full text |Cite
|
Sign up to set email alerts
|

Can Rapid Diagnostic Testing for Malaria Increase Adherence to Artemether–Lumefantrine?: A Randomized Controlled Trial in Uganda

Abstract: Abstract. Most patients with suspected malaria do not receive diagnostic confirmation before beginning antimalarial treatment. We investigated the extent to which uncertainty about malaria diagnosis contributes to patient nonadherence to artemether-lumefantrine (AL) treatment through a randomized controlled trial in central Uganda. Among 1,525 patients purchasing a course of AL at private drug shops, we randomly offered 37.6% a free malaria rapid diagnostic test (RDT) and then assessed adherence through home v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…A randomized, cross-cutting intervention was conducted in which a rapid diagnostic test (RDT) for malaria was offered to 25% of patients at the time they purchased ACTs. We evaluate the impact of diagnostic testing on adherence in a separate paper and show that a confirmed diagnosis of malaria had no significant effect on adherence ( Saran et al, 2016 ). For the analysis of the packaging and messaging treatments presented here, we always control for the (orthogonal) RDT offer and present robustness checks showing the impact of the treatment arms for the 75% of patients who were not randomly assigned to be offered testing.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…A randomized, cross-cutting intervention was conducted in which a rapid diagnostic test (RDT) for malaria was offered to 25% of patients at the time they purchased ACTs. We evaluate the impact of diagnostic testing on adherence in a separate paper and show that a confirmed diagnosis of malaria had no significant effect on adherence ( Saran et al, 2016 ). For the analysis of the packaging and messaging treatments presented here, we always control for the (orthogonal) RDT offer and present robustness checks showing the impact of the treatment arms for the 75% of patients who were not randomly assigned to be offered testing.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…A study in Uganda in 2016 reinforced this idea as it found no association between testing and treatment adherence as long as the treatment sent by shop vendors was associated with treatment information. 31 Beside the lack of treatment information, the high cost of the treatment on the black market is another factor leading to poor adherence. In fact, ACTs cost 1 to 3 grams of gold (25 to 90 USD), when miners gain about 10 to 15 grams per week.…”
Section: Malaria Treatment Adherence Is Better When It Is Cheap and Dmentioning
confidence: 99%
“…For example, although the packaging was part of the outcome definition, the proportion of packaging available was not reported in a number of studies [ 35 , 41 , 42 ]. In others, the package information although collected, was not utilized and only self-reported (probable) adherence rates were reported [ 44 , 63 , 64 ]. In Ghana, an intervention study used package inspection as a secondary outcome to validate self-reported adherence, but found that only 60% of patients were able to produce their package, suggesting that this may not be the most accurate measurement of ACT adherence [ 36 ].…”
Section: Discussionmentioning
confidence: 99%